ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH PERSAMAAN KUADRAT PADA PEMBELAJARANMODEL CREATIVE PROBLEM SOLVING - Purwati, Ratna; Hobri, Hobri; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2016)
Abstract. Critical Thinking Skills is very important for us because critical thinking skills can be used to solve problems and as a judgement in right decision making. One of the methods used to equip students with critical thinking skills is using Creative Problem Solving (CPS) model in mathematics class. This research is a qualitative descriptive research aimed to describe the critical thinking skills of students in X-Class using CPS model in solving quadratic equations problems and the provision of scaffolding. The subject of this research is students of SMK N 2 Jember grade 10 (X-Class). The method of data collecting used in this research is critical thinking skills test and interview. Analysis of students critical thinking skills test is based on critical thinking skills indicat by Facione determined by the researcher. The results of this research showed that sudents critical thinking skills in X-TPM Class at SMK Negeri 2 Jember generally can be grouped into 3 categories are high, average, and low critical thinking skills. Students with high critical thinking skills satisfy all of crtitical thinking skills indicarors. Students with average critical thinking skills can only satisfy interpretation and analysis indicators. But less capable in evaluation and inference indicators. Whereas, the students with low critical thinking skills are less capable in interpreting the problem and they can't satisfy analysis, evaluation, and inference indicators. Keywords: Critical Thinking, Creative Problem Solving.